Facial Growth of Patients With Complete Unilateral Cleft Lip and Palate Treated With Alveolar Bone Grafting at 6 Years. (May 2019) - Doucet, Jean-Charles; Russell, Kathleen A.; Daskalogiannakis, John; Mercado, Ana M.; Emanuele, Nicholas; James, Lindsay; Hathaway, Ronald R.; Long, Ross E.
Objective: To investigate the effect that alveolar bone grafting (ABG) around 6 years of age has on facial growth by assessing craniofacial growth outcomes. Design: Retrospective cohort study. Setting: North American cleft centers. Participants: A total of 33 children with complete unilateral cleft lip and palate who were consecutively treated with secondary ABG around 6 years of age were compared to 148 participants from 4 centers with late secondary ABG. Methods: Preorthodontic standardized lateral cephalometric radiographs were analyzed and traced according to the Americleft Study protocol. Sixteen angular and 2 proportional measurements were performed. The outcomes of all ABG were assessed using the Standardized Way to Assess Graft scale. Measurement means from the study center (SC) were compared to 4 North American centers using analysis of variance and Welch modified t tests, and P < .05 was considered statistically significant. Results: For the SC, the mean age (SD) at the time of bone graft was 5.85 (0.71) years and the mean age at the time of the lateral cephalogram was 13.4 (1.8) years. The sagittal maxillary prominence of the SC was comparable to the 4 other centers. The mean SNA (78.1 [4.3]) for the SC was significantly higher compared to one center that used primary bone grafting ( P = .03). The soft tissue mean ANB (3.52 [4.09]) for the SC was significantly lower compared to 3 of the centers. Conclusions: Early secondary ABG around 6 years of age did not result in reduced midface projection as assessed by SNA and thus did not compromise anterior maxillary growth.